2010
DOI: 10.1071/zo09084
|View full text |Cite
|
Sign up to set email alerts
|

Molar crests and body mass as dietary indicators in marsupials

Abstract: The discovery of ecomorphological relationships in mammals is important not only in its own right, but also for its potential in shedding light on the ecology of extinct and poorly known species. Two such potential relationships are the proposed connection between molar shear crests and body mass to diet. Research on primates suggests that, owing to the digestive challenges of structural carbohydrates (in foliage and insects), folivores and insectivores differ from other species in needing relatively long mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…Cartmill related these features to the use of the anterior upper incisors in biting through wood to extract wood-boring insect larvae. Additionally, Hogue (2008) found that marsupial folivores show an increase in the vertical bending strength of the mandibular corpus similar to results predicted from the primate literature, and Kay and Hylander (1978) and Hogue and ZiaShakeri (2010) found that molar morphology in marsupials replicates patterns previously observed in primates with regard to the summed length of molar crests.…”
supporting
confidence: 72%
“…Cartmill related these features to the use of the anterior upper incisors in biting through wood to extract wood-boring insect larvae. Additionally, Hogue (2008) found that marsupial folivores show an increase in the vertical bending strength of the mandibular corpus similar to results predicted from the primate literature, and Kay and Hylander (1978) and Hogue and ZiaShakeri (2010) found that molar morphology in marsupials replicates patterns previously observed in primates with regard to the summed length of molar crests.…”
supporting
confidence: 72%
“…One issue not addressed by our study is the potentially important role that dental form plays in chewing investment and cyclical loading. Mammals that masticate tough leaves tend to have long, well-developed molar shearing crests, whereas species that exploit hard fruits and seeds tend to have bunodont teeth with much shorter and blunter crests ( Kay, 1975 ; Kay, 1978 ; Walker & Murray, 1975 ; Sheine & Kay, 1977 ; Sheine & Kay, 1982 ; Strait, 1998 ; Hogue & ZiaShakeri, 2010 ). Because “the working surface of the molars have a strong effect on the physiological rate of breakdown” ( Lucas, 2004 , p. 167), it is likely that variation in molar relief translates into intra- and interspecific disparities in chewing investment for different types of foods.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum body size for obligate marsupial and placental browsers is ∼500 g [94], [95]. Obligate insectivores require body sizes smaller than the threshold for browsers due to the size and patchiness of their food sources, with the exception of specialists feeding on colonial insects (i.e.…”
Section: Resultsmentioning
confidence: 99%